Overwintering and cold tolerance in the moor frog (Rana arvalis, Anura) across its range - Berman, Daniil I.; Bulakhova, Nina A.; Meshcheryakova, Ekaterina N.; Shekhovtsov, Sergey V. (NRC Research Press (a division of Canadian Science Publishing), 2020)
Only two species of boreal Holarctic frogs (genus Rana Linnaeus, 1758) can survive freezing and overwinter on land; they are found in the subarctic and cold regions of North America (Wood Frog, Rana sylvatica LeConte, 1825) and Eurasia (Moor Frog, Rana arvalis Nilsson, 1842) and are an example of an unusual adaptive strategy of overwintering. Freeze tolerance (down to –16 °C) of R. sylvatica has been thoroughly studied; however, little is known about cold resistance of R. arvalis in cold regions. We found that R. arvalis from European Russia and from West Siberia tolerate freezing down to –12 or –16 °C, whereas frogs from the Danish population survived freezing only to –4 °C (Y. Voituron et al. 2009b; J. Comp. Physiol. B, 179: 223–230). All of these populations, according to mitochondrial DNA markers, are closely related. We suggest that the observed differences in cold tolerance (–4 °C vs. –12 or –16 °C) could be caused either by adaptations to climatic factors or by differences in experimental protocols. The northeastern boundary of the geographic range of R. arvalis in Yakutia coincides with the transitional area between discontinuous and continuous permafrost; beyond this area, winter soil temperature sharply declines. The lower lethal temperature and overwintering ecology of R. arvalis in Siberia are similar to those of the North American R. sylvatica. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.